Analysis Of An Order Fulfilment Process At A Metalwork Company Using Different Lean Methodologies - Dias, José António (2020)
This article presents the analysis of a process by using four distinct approaches, each of them recurring to different Lean tools in order to get a detailed and multidimensional overview of the process. The primary objective of this study was to identify activities which add value in the order fulfilment process of a metalwork company. In this context, one also addressed issues such as waste, problems and their causes, in order to define intervention priorities and select actions capable to enhance the performance and efficiency of the process. The secondary objective was to evaluate and compare the results of the analysis made through different mapping techniques. From this study results the proposal of a tool to identify perceived micro-inefficiencies, as well as the impact of these on the production sub-process. Designated as Perceived Waste Mapping (PWM), this method allowed one to estimate that the ratio between the value-added hours and the total number of work hours at the company will be approximately 30%, far from the figure of 84% registered in the existing time and production records.